2012 7th IEEE International Symposium on Applied Computational Intelligence and Informatics (SACI) 2012
DOI: 10.1109/saci.2012.6250035
|View full text |Cite
|
Sign up to set email alerts
|

VS-type stabilization of MRAC controllers using robust fixed point transformations

Abstract: Nowadays, control of dynamical systems with uncer tainties is a common problem. Many sulutions can be found in the literature, one of these methods is the family of Robust Fixed Point Transformations (RFPT) with local basin of attraction.The method is based on the idea that if someone has to use an approximate model in a control task, there is a function which, locally converging to the right solution, can reduce the disadvantages of the approximation. In this paper, authors show that though RFPT can loose its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The behavior of the sequence {Q Def n } outside the region of convergence depends on the global properties of G. In [19], a chattering-like behavior was accidentally found and was further analyzed in [20]. A more detailed analysis in [21] revealed that the following cases may happen: a) monotone or non-monotone convergence to the solution of the control task, b) bounded chaotic behavior that can be treated by the method outlined in [19], c) divergence to infinity, d) convergence to the trivial fixed point of G i.e., to −K c .…”
Section: Possible Divergences Of the Rfpt-based Controllersmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of the sequence {Q Def n } outside the region of convergence depends on the global properties of G. In [19], a chattering-like behavior was accidentally found and was further analyzed in [20]. A more detailed analysis in [21] revealed that the following cases may happen: a) monotone or non-monotone convergence to the solution of the control task, b) bounded chaotic behavior that can be treated by the method outlined in [19], c) divergence to infinity, d) convergence to the trivial fixed point of G i.e., to −K c .…”
Section: Possible Divergences Of the Rfpt-based Controllersmentioning
confidence: 99%
“…A more detailed analysis in [21] revealed that the following cases may happen: a) monotone or non-monotone convergence to the solution of the control task, b) bounded chaotic behavior that can be treated by the method outlined in [19], c) divergence to infinity, d) convergence to the trivial fixed point of G i.e., to −K c .…”
Section: Possible Divergences Of the Rfpt-based Controllersmentioning
confidence: 99%
“…[72]) that help keeping the controlled system in the region of convergence. It have been also shown that quitting the region of convergence cannot result in catastrophic aftermaths: the controller can still work with considerable chattering that can be reduced and evaded [73], [74]. 7) Finally, these controllers can behave in a cognitive way that besides applying iterative corrections to a given approximate model they can select various approximate models by observing the behavior of the controlled systems.…”
Section: General Characteristics Of Cognitive Control -What To Domentioning
confidence: 99%
“…At the beginning, only the local properties of this transformation were investigated in the vicinity of the fixed point, and various tuning methods were suggested for keeping the control signal in the basin of attraction of the useful fixed point [11], [12]. Later its global properties were investigated in [13], [14], [15] and [16]. The conclusion of these investigations was that for a wide class of physical systems it was possible to so tune only one of the altogether three adaptive control parameters that monotone convergence to the useful fixed point could be maintained.…”
Section: Introductionmentioning
confidence: 99%